A large intracardiac fungus ball in a premature infant - Ekici, Filiz; Varan, Birgül; Şaylan-Çevik, Berna; Özkan, Murat; Ok-Atılgan, Alev; Oktay, Ayla (The Turkish Journal of Pediatrics, 2011)
We present a premature infant with large intracardiac mass. She had a history of sepsis and umbilical venous catheterization in the neonatal period. Twenty-seven days after withdrawal of the catheter, a precordial murmur was noted. A large right atrial highly mobile mass suspected to be thrombus was detected by echocardiography. C-reactive protein was elevated. Three blood cultures were negative. Anticoagulation treatment was started. After one week, no resolution of the thrombus was observed. The mass was surgically resected and diagnosis of thrombus infected by fungi was made on histopathological examination. Early screening of cardiac chambers by echocardiography is recommended in all preterms with intravascular catheterization.